The role of business grant assistance, micro saving and financial knowledge towards Bumiputera SME business performance in Sabah - Mat Salleh Ayub; Mohd Affandi Harun; Mazalan Mifli; Azmi Majid (Asian Scholars Network, 2020)
The purpose of this study is to examine the influence of business grant, micro saving, and financial knowledge towards Bumiputera SME business performance in Sabah. This paper analyses the Bumiputera SME performance by examining three determinants, namely business grant assistance, micro saving and financial knowledge. Total number of 187 questionnaires distributed and 96 were returned. The respondents were selected from TERAJU (Sabah) SMEs directory database and respondents were those who have been assisted and supported by TERAJU programs. The data collected and analyzed using Statistical Package for the Social Science (SPSS 26) and SmartPLS 3.0. The study confirms that there are significant positive relationships between micro saving towards Bumiputera SME performance in Sabah. However, the study also found that there are no significant relationships between financing knowledge and business grant assistance towards Bumiputera SME business performance in Sabah. The finding of this study has useful implication to help strengthen the provision of government business support to Bumiputera SME in Sabah. It will provide new framework for future study on SMEs business performance looking at the SMEs business support ecosystem in Sabah.